Optimasi Pertanian: Sosialisasi Budidaya Sayuran Organik Untuk Peningkatan Kesejahteraan Petani Dan Kualitas Pangan - Muhammad Ikhsan Fitrianata; Mirza Andrian Syah (Lembaga Pengembangan Kinerja Dosen, 2024)
Cultivating organic vegetables promises significant benefits such as supporting environmental health, increasing farmer welfare, and improving food quality. Even though demand for organic vegetables continues to increase, farmers' awareness and understanding regarding organic cultivation is still limited due to barriers to access to information and the strong tradition of conventional farming. To overcome these obstacles, service activities are carried out through socialization of organic vegetable cultivation, in collaboration with CV Reja Mayur. This outreach not only provides technical information on organic cultivation but also highlights economic and environmental aspects. Approach methods through lectures, discussions and simulations are used to provide significant understanding to socialization participants. The results of this activity are not only aimed at meeting market demand for organic vegetables, but also as a strategic step in achieving sustainable agriculture. The hope is that farmers can implement organic vegetable cultivation practices with sufficient confidence and knowledge, create positive transformations in their lives, and have a positive impact on the local community and environment.